2005
DOI: 10.1007/s10608-005-0511-1
|View full text |Cite
|
Sign up to set email alerts
|

It’s All About Me: Self-Focused Attention and Depressed Mood

Abstract: The present study examined self-focused attention in dysphoria under various mood conditions. Participants were randomly assigned to either a positive, negative, or neutral writing condition. Results indicated that dysphoric participants displayed significantly greater self-focused attention across all conditions relative to the non-dysphoric participants. Taken together, these findings indicate that heightened self-focused attention is a pervasive pattern in dysphoric persons that may contribute to maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 32 publications
3
32
0
1
Order By: Relevance
“…Compared with other people, depressed people are known to focus more on internal signals than on external circumstances (Sloan, 2005). Therefore we expected the children in our study to pay more attention to their bodily signals than to the emotional impact of the situation, and to display a coping focus in line with this attention bias.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Compared with other people, depressed people are known to focus more on internal signals than on external circumstances (Sloan, 2005). Therefore we expected the children in our study to pay more attention to their bodily signals than to the emotional impact of the situation, and to display a coping focus in line with this attention bias.…”
Section: Discussionmentioning
confidence: 96%
“…A tendency for depression, on the other hand, may very well elicit an enhanced physiological coping focus. Depressed people are known to focus more on their internal signals than on the outside world (Sloan, 2005). Consequently, they will be more likely to explicitly notice their bodily signals more often than others.…”
Section: Introductionmentioning
confidence: 99%
“…For example, those who write about resolved events use more past tense words (Pasuputhi, 2007); more past tense and fewer present tense words are linked with decreased grief and trauma (Boals & Klein, 2005;Pillemer, Desrochers & Ebanks, 1998). First-person singular pronouns (e.g., I, me) are related to depression (e.g., Gortner & Pennebaker, 2004;Sloan, 2005). More positive than negative emotion words as well as more meaning-making words (cause and insight) indicate recovery from emotional trauma (i.e., they have cognitively processed the event and are moving toward feeling more positive than negative) and are linked to health and well-being (e.g., Pennebaker, Mehl, & Niederhoffer 2003).…”
Section: Linguistic Markersmentioning
confidence: 99%
“…Previous work has shown that language positivity is aligned with the mood of the author, i.e., happier people use more positive language (20,21,38,39). Although these findings were based on the writings of individual subjects, we hypothesize that the same pattern should be observable in group-level time series.…”
Section: Short-term Fluctuations In Lpbmentioning
confidence: 99%
“…Others have argued that the evaluative content of language might express people's current affective state (19)(20)(21). Because humans tend to show an affective bias toward positivity (22-24)-a phenomenon often referred to as the "positivity offset" (25)-it is plausible to see LPB as a reflection of a lower-level bias toward subjective positive affect (12,26,27).…”
Section: Significancementioning
confidence: 99%